OPG/RANKL/RANK gene methylation among alcohol-induced femoral head necrosis in northern Chinese men - Tiantian Wang; Fei Wang; Tingting Liu; Menghu Sun; Feimeng An; Chang Liu; Ye Tian; Yuju Cao; Jianzhong Wang (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background and purpose Alcohol-induced osteonecrosis of the femoral head (ONFH) is a complex and heterogeneous disease. Genetic factors and epigenetic modifications are one of the pathogenesis of the disease. However, the influence of epigenetic factors on the disease has not been systematically studied. Our research aims to determine the methylation changes of alcohol-induced ONFH. Methods An analytical cross-sectional study of a Chinese male population (50 alcohol-induced ONFH patients and 50 controls). The EpiTYPER of the Sequenom MassARRAY platform was used to detect the DNA methylation status of 132 cytosine-phosphate-guanine (CpG) sites in the OPG/RANKL/RANK gene promoter region. Results In the whole study group, the chi-square test was used to analyze the methylation rate between the two groups, and six CpG sites were found to be different, among which OPG1_CpG_2, OPG3_CpG_4, RANK1_CpG_6, RANK3_CpG_10, RANKL2_CpG_21, and RANKL2_CpG_46 in the case group were higher than those in the control group, while OPG4_CpG_2 was lower than that in the control group. The results showed that in patients with alcohol-induced ONFH, 146 CpG sites were examined for differences in methylation levels compared with healthy controls, 32 of which were not detected, and 23 of the remaining 114 sites showed differences in methylation levels compared with alcohol-induced ONFH patients. Receiver operator characteristic (ROC) curve analysis demonstrated the methylation levels of OPG/RANKL/RANK could efficiently predict the existence of alcohol-induced ONFH. Conclusion Our study of Chinese men suggests that several CpG sites in the OPG/RANKL/RANK gene in peripheral blood leukocytes of patients with alcohol-induced ONFH are in an abnormal methylation state (hypermethylation tended to be more frequent).